Knowledge and Practices of Periodontal Health and Oral Hygiene among BDS Students - Malla, Suprim; Shrestha, Reshma; Dhami, Bhageshwar; Gupta, Sujaya; Deo, Satish (Journal of Nepalese Society of Periodontology and Oral Implantology, 2017)
Background: Periodontal disease is an inflammatory oral disease that affects the soft and hard tissues supporting the teeth. Gingivitis, an early stage, when untreated leads to periodontitis that causes progressive tooth mobility leading towards tooth loss. Periodontitis is ubiquitous and commonly manifests in adult life. Early detection of oral diseases makes them more amenable to treatment and allows better chance of cure. BDS students are young adults who are going to be future oral health care provider. Their knowledge and oral hygiene practices may impact oral health status of a society. Aims: The aim of this study was to evaluate the knowledge of oral health and periodontal disease and correlate it with oral hygiene practices among BDS students not exposed to clinical practice. Materials and Methods: This cross-sectional study was carried out among 120 students of first, second and third year BDS at Kantipur Dental College. The students who were not exposed to clinical practice were invited to participate. The data was collected by self-administered structured questionnaire. There were total of 15 questions on knowledge and oral hygiene practice and scores were assigned to each question. Data analysis was done by SPSS 20 software program. Results: The mean knowledge score of the population was 6.58 ± 1.29 and mean practice score as 6.20 ± 1.73. The participants had good knowledge (55%) of oral health and periodontal diseases. However, only 22.5% of participants followed good oral hygiene practices. There was no significant difference of knowledge between males and females (p = 0.831) but a statistically significant difference was seen in the practice of oral hygiene (p = 0.006). Conclusion: Despite having good knowledge (55%) of oral and periodontal health, 77.5% of the BDS students did not follow good oral hygiene practices on a regular basis. Dental students must be encouraged to be good role models in practicing as well as promoting oral health. The authors would like to recommend incorporating some oral health and preventive dentistry topics in the non-clinical BDS curriculum.